Her Sweet Revenge - Bonner, Sarah (New York : Grand Central Publishing, 2023)
"Two women receive the same anonymous note. For one, it's a threat. For the other, it's an invitation for revenge. Helena is beautiful, successful, and living in married bliss in Exeter. But she's hiding a secret that could tear her perfect life apart. When the notes begin to arrive, she realizes someone else must know. But what might her husband and his overbearing family do if they find out the truth? Thea is reeling from her best friend Helena's death. But when she starts digging into the circumstances, she receives a threatening note warning her to stop. She knows her friend's death wasn't an accident. This was murder. And she is determined to get revenge"--
Keywords: Revenge -- Fiction; Thrillers (Fiction); Novels